Keys for Improving Citizens’ Satisfaction with Public Services of Local Government - Mohamed Almihat; Ma. June S. Carlos; Edwin T. Caoleng; Patricia Ann D. Estrada (African Journal of Advanced Pure and Applied Sciences, 2022)
The people, companies, and workers in both the public and private sectors make up the large consumer base of the government. The government offers information and services to each group of its customers via its agencies, departments, and ministries, it was further said, therefore the only people who can objectively assess its success are the people who use it. Customer satisfaction is the primary criterion for assessing the quality of the product or service, as well as the ancillary services and key performance indicators of public organizations, that are supplied to clients. In order to enhance the quality of a product or service and provide a firm with a competitive edge, measuring customer satisfaction is an essential component of the process. Therefore, this paper reviews the importance of delivering good quality services to the citizens. The first section gives an overview of the relationship and trust between consumers and the government. While second part addresses the role of Local government in prompting e-government and ensuring citizens’ privacy and security. Finally, discussing improving the public services delivery and the way forward in the modern era. Hence, the contribution of this paper mainly focused on investigating the public services, it opens more opportunities for further research in the field of citizen’s satiation and local government.